Subjective Age and Mortality in Three Longitudinal Samples. Issue 7 (September 2018) - Stephan, Yannick; Sutin, Angelina R.; Terracciano, Antonio
ABSTRACT: Objective: Subjective age has been implicated in a range of health outcomes. The present study extends existing research by providing new data on the relation between subjective age and mortality in three large national samples. Methods: Participants ( N > 17, 000) were drawn from the Health and Retirement Study (HRS, 2008–2014), the Midlife in the United State Survey (MIDUS, 1995–2014), and the National Health and Aging Trends Study (NHATS, 2011–2014). Subjective age, demographic factors, disease burden, functional limitations, depressive symptoms, and physical inactivity were assessed at baseline, and mortality data were tracked for up to 20 years. Cognition was also included as a covariate in the HRS and the NHATS. Results: Individuals felt on average 15% to 16% younger relative to their chronological age. Feeling approximately 8, 11, and 13 years older in the MIDUS, HRS, and NHATS was related to an 18%, 29%, and 25% higher risk of mortality, respectively. This pattern was confirmed by a meta-analysis of the three samples (hazard ratio, 1.24; 95% confidence interval, 1.17–1.31; p < .001). Multivariate analyses showed that disease burden, physical inactivity, functional limitations, and cognitive problems, but not depressive symptoms, accounted for the associations between subjective age and mortality. Conclusions: The present study provides robust evidence for an association between an older subjective age and a higher risk of mortality across adulthood. These findings support the role of subjective age as a biopsychosocial marker of aging. Abstract : Supplemental digital content is available in the text.